MONITORING OF FIRE OUTBREAKS IN THE LEGAL AMAZON REGION OF MARANHÃO IN THE MUNICIPALITIES OF THE PINDARÉ-MA VALLEY - Santos, Angela Maria Corrêa Mouzinho; Carneiro, Eva Dayna Felix; Sodré, Antonio Marcos Nogueira; Brito, Ronilson Lopes; Souza, Franscristhiany Silva; Silva, Flavio Evangelista; Martins, Paulo Henrique Amorim (Seven Editora, 2026)
The Microregion of the Pindaré Valley comprises 22 municipalities and is named after one of the longest and most important rivers in Maranhão, the Pindaré River. This study aimed to analyze the occurrence of wildfires in the municipalities of the Pindaré Valley that are part of the Legal Amazon. The adopted methodology involved collecting information from the Meteorology Database - BDMEP, National Institute for Space Research - INPE, Brazilian Institute of Geography and Statistics - IBGE, Institute of Applied Economics - IPEA, Center for Weather Forecasting and Climate Studies - CPTEC for the period 2018-2022. The BDQueimadas and Environmental Information Bank (BDiA) verified that the municipalities of Santa Luzia, Buriticupu, and Bom Jardim had the highest number of fire outbreaks, due to their phytoecological characteristics and the predominance of Dense Ombrophilous Forest. Meanwhile, the municipalities of Tufilândia and Pindaré Mirim recorded the lowest number of outbreaks, reflecting a region predominantly composed of Open Ombrophilous Forest. It was observed that most municipalities engage in agropastoral activities and use fire to clear pastures due to its low cost. The analysis also revealed that the first semester has higher average rainfall and lower temperatures, whereas in the second semester the situation is reversed. Therefore, the variables temperature, rainfall, vegetation cover, and agropastoral activities may significantly influence the increase in fire outbreaks. Implementing environmental control and fire prevention measures is essential for sustainable development and the ecological balance of these communities.DOI: https://doi.org/10.56238/sevened2026.008-086